2015
DOI: 10.1016/j.jval.2015.09.2121
|View full text |Cite
|
Sign up to set email alerts
|

Basal Insulin Persistence, Associated Factors, and Outcomes After Treatment Initiation Among People With Type 2 Diabetes Mellitus In Japan

Abstract: A611within and between the MTM members and controls were measured (differencein-differences (DID) analysis). Results: 2382 patients (MTM group: n= 201, mean age= 75,44%male; control group: n= 2181,mean age= 74,48%male) in the diabetes cohort and 9751 patients (MTM group: n= 563, mean age= 76,39% male; control group: n= 9188, mean age= 75,40% male) in the hypertension cohort were included. For patients in diabetes cohort, the MTM group had pre-post increase in PDC by 5.19% (P= 0.05), while the control group had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
0
17
2
1
Order By: Relevance
“…Three studies defined a gap of 30 days as demonstrating nonpersistence,17,23,24 while one defined a longer gap of 90 days 13. Two studies provided a definition of “interrupters” as patients who received at least one prescription after a gap 17,24. A data-driven approach to the measurement of persistence was taken in one study, again due to the issues of using days supply encountered with injectable treatments 11…”
Section: Resultsmentioning
confidence: 99%
“…Three studies defined a gap of 30 days as demonstrating nonpersistence,17,23,24 while one defined a longer gap of 90 days 13. Two studies provided a definition of “interrupters” as patients who received at least one prescription after a gap 17,24. A data-driven approach to the measurement of persistence was taken in one study, again due to the issues of using days supply encountered with injectable treatments 11…”
Section: Resultsmentioning
confidence: 99%
“…Poor treatment adherence and persistence have been shown to affect the real-world effectiveness of insulin and negatively impacts desired clinical and economic outcomes [5][6][7][8][9][10][11][12][13]. While several studies have examined persistence with basal insulin treatment [8,10,[14][15][16][17][18][19][20][21], few studies have explored the patients' reasons for continuing treatment [19] or distinguished among patients who temporarily interrupted therapy versus those who discontinued insulin completely [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This may partly be attributed to poor persistence to insulin therapy, defined as the duration of time from initiation to discontinuation of treatment or the proportion of patients who continued treatment for a specific time . Previous studies also revealed discontinued basal insulin (BI) treatment incurred higher medical resource use and costs than continuers . While several studies have examined factors associated with insulin treatment persistence such as age, comorbidity, type of initiated insulin and concomitant antidiabetic drug use, few studies have explored the patients' reasons for discontinuing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have examined factors associated with insulin treatment persistence such as age, comorbidity, type of initiated insulin and concomitant antidiabetic drug use, few studies have explored the patients' reasons for discontinuing treatment. In addition, most studies assessed persistence patterns using retrospective claims rather than actual medication‐taking behaviour . The limited information hinders better management of treatment after initiating insulin to improve patients' persistence with insulin treatment.…”
Section: Introductionmentioning
confidence: 99%